Productivity shocks, monetary shocks, and the short- and long-run dynamics of exchange rates and relative prices - Michael Bergman; Yin-Wong Cheung; Kon S. Lai (Lund University, School of Economics and Management, Department of Economics, 2000)
This study evaluates the individual roles of monetary and productivity shocks in real exchange rate fluctuations under the current float. Using a cointegration model of exchange rates and relative prices, the innovations are decomposed into transitory and common-trend parts. Both transitory and common-trend innovations are found to explain a significant portion of real exchange rate fluctuations, albeit their relative importance can vary across major currencies. Further analysis suggests that common-trend innovations are ascribed mostly to productivity shocks, whereas transitory innovations are governed by monetary shocks. The allowance for productivity shocks, however, appears insufficient to fully explain the high persistence of real exchange rates.
Keywords: F31; F41; 330; Real exchange rate; real shock; monetary shock; transitory component; common trend